Political Marketing and Identity Politics: Implications for Voter Engagement and Interest - Sarofah, Riska; Putra, Nauval Trian; Saputra, Herdin Arie (Nyimak: Journal of Communication, 2024)
This study examines the impact of identity-based political marketing on voter interest in Tasikmalaya City for the 2024 Legislative Elections. Using a quantitative research design with a survey approach, data were collected through questionnaires distributed to a randomly selected sample from the city's official voter list. Multiple linear regression analysis was employed to assess the relationship between identity-based political marketing strategies (independent variables) and voter interest (dependent variable). The findings indicate that identity-based political marketing strategies—which include ethnic, religious, and cultural factors—significantly influence voter interest. This underscores the critical role of identity politics in shaping voter preferences in Tasikmalaya City. These results suggest that political parties and legislative candidates should tailor their campaign strategies to align with the local voter identity dynamics. Understanding the complexity of identity politics is essential for political actors to formulate effective and relevant campaign strategies. A deep understanding of how identity factors influence voter engagement can enhance voter participation and promote a more inclusive and representative democratic process. This research provides valuable insights into how identity politics can be strategically leveraged to influence election outcomes. Keywords: Political Marketing, Identity Politics, Voter Interest, Legislative Elections, AbstrakPenelitian ini mengkaji dampak pemasaran politik berbasis identitas terhadap minat pemilih di Kota Tasikmalaya untuk Pemilihan Legislatif 2024. Menggunakan desain penelitian kuantitatif dengan pendekatan survei, data dikumpulkan melalui kuesioner yang disebarkan kepada sampel yang dipilih secara acak dari daftar pemilih tetap (DPT) kota tersebut. Analisis regresi linier berganda digunakan untuk menilai hubungan antara strategi pemasaran politik berbasis identitas (variabel independen) dan minat pemilih (variabel dependen). Temuan menunjukkan bahwa strategi pemasaran politik berbasis identitas—yang mencakup faktor etnis, agama, dan budaya—secara signifikan memengaruhi minat pemilih. Hal ini menegaskan peran penting politik identitas dalam membentuk preferensi pemilih di Kota Tasikmalaya. Hasil ini menyarankan agar partai politik dan calon legislatif menyesuaikan strategi kampanye mereka dengan dinamika identitas pemilih lokal. Memahami kompleksitas politik identitas penting bagi aktor politik untuk merumuskan strategi kampanye yang efektif dan relevan. Pemahaman yang mendalam tentang bagaimana faktor identitas memengaruhi keterlibatan pemilih dapat meningkatkan partisipasi pemilih dan mendorong proses demokrasi yang lebih inklusif dan representatif. Penelitian ini memberikan wawasan berharga tentang bagaimana politik identitas dapat dimanfaatkan secara strategis untuk memengaruhi hasil pemilihan.Kata Kunci: Marketing Politik, Politik Identitas, Minat Pemilih, Pemilu Legislatif,